Cognitive presentation of multiple sclerosis: evidence for a cortical variant. Issue 7 (1st July 2003) - Zarei, M; Chandran, S; Compston, A; Hodges, J
Abstract : Background: Although neuropsychiatric complications are well recognised, the presentation of multiple sclerosis with cognitive or neuropsychiatric symptoms has generally been considered a rare occurrence and to reflect subcortical pathology. Objectives: To document the clinical, neuropsychological, and radiological features of six cases of cognitive presentation of multiple sclerosis, to review the relevant literature, and to propose a possible cortical basis for this clinical presentation. Subjects: Six patients (five women; age range 38 to 60 years) presented to the memory and cognitive disorders clinic in Cambridge with an initially undiagnosed cognitive/neuropsychiatric syndrome. All underwent neuropsychological evaluation, brain imaging, and ancillary investigations to establish a diagnosis of multiple sclerosis. Results: The six cases all had a progressive dementia syndrome with prominent amnesia, often accompanied by classic cortical features including dysphasia, dysgraphia, or dyslexia. Mood disturbance was ubiquitous and in three patients there was a long history of preceding severe depression. All six developed characteristic physical signs on follow up, with marked disabilities. A review of 17 previously reported cases highlighted the prominence of memory impairment and depression in the early stages. Conclusions: On clinical, pathological, and radiological grounds, the neuropsychiatric presentation of multiple sclerosis may represent a clinicopathological entity of "cortical multiple sclerosis." Failure to recognise this will delay diagnosis and may expose patients to potentially dangerous and invasive investigation. Because the neuropsychiatric features of cortical multiple sclerosis are a major cause of handicap, their early recognition may be particularly important in view of emerging treatments.